Physicochemical stability of nefopam and nefopam/droperidol solutions in polypropylene syringes for intensive care units. Issue Volume 27:Issue e1(2020) (11th June 2019) - D'Huart, Elise; Vigneron, Jean; Clarot, Igor; Demoré, Béatrice
Abstract : Introduction: Nefopam has been reported to be effective in postoperative pain control with an opioid-sparing effect, but the use of nefopam can lead to nausea and vomiting. To prevent these side effects, droperidol can be mixed with nefopam. In intensive care units, high concentrations of nefopam and droperidol in syringes can be used with a continuous flow. Objectives: The first objective of this work was to study the physicochemical stability of a nefopam solution 2.5 mg/mL diluted in NaCl 0.9% in polypropylene syringes immediately after preparation and after 6, 24 and 48 hours at room temperature. The second objective was to study the physicochemical stability of mixtures of nefopam 2.5 mg/mL and droperidol 52 µg/mL diluted in NaCl 0.9% in polypropylene syringes at room temperature over 48 hours. Materials and methods: Three syringes for each condition were prepared. For each time of analysis, three samples for each syringe were prepared and analysed by high performance liquid chromatography coupled to photodiode array detection. The method was validated according to the International Conference on Harmonisation Q2(R1). Physical stability was evaluated by visual and subvisual inspection (turbidimetry by UV spectrophotometry). pH values were measured at each time of analysis. Results: Solutions of nefopam at 2.5 mg/mL and the mixture of nefopam 2.5 mg/mL with droperidol 52 µg/mL, diluted in NaCl 0.9%, without protection from light, retained more than 90% of the initial concentration after 48 hours storage at 20–25°C. No modification in visual or subvisual evaluation and pH values were observed. Conclusion: Nefopam solutions at 2.5 mg/mL and the mixture of nefopam 2.5 mg/mL with droperidol 52 µg/mL diluted in NaCl 0.9% were stable over a period of 48 hours at room temperature. These stability data provide additional knowledge to assist intensive care services in daily practice.